Recurrent pancreatitis after unremarkable colonoscopy, temporalised by CT imaging: an unusual case. (8th January 2016) - Limb, Christopher; Ibrahim, Ibrahim A K; Fitzsimmons, Sophie; Harper, Ashton J
Abstract : Acute pancreatitis is a common surgical presentation, frequently caused by gallstones and alcohol. Here we present an unusual case of a recurrent episode of pancreatitis after an unremarkable colonoscopy, in a patient with several pre-existing risk factors for pancreatitis. Before and after abdominal CT scans clearly demonstrate the acute inflammatory process affecting the pancreas and temporalise its development. Early resuscitation and appropriate involvement of high dependency care is advocated by all current guidelines to improve patient outcome. We consider possible aetiology and how early diagnosis and recognition of possible high-risk situations can expedite its investigation and management, helping to provide the best possible care.